2020
DOI: 10.3390/app10186225
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Dehydration for the Production of Novel Pumpkin Cut Products of Enhanced Nutritional Value and Sustainability

Abstract: The quality and preservability of fresh-cut fruits can be improved by osmotic dehydration (OD). In this study, the impact of Strained Yoghurt Whey (SY Whey) (along with other osmotic solutes) on mass transfer kinetics (water loss, solid gain, water activity decrease), quality attributes (color, texture, sensory characteristics, vitamin C), and microbial stability during OD and subsequent refrigerated storage (5–15 °C) of OD-processed pumpkin cuts was studied. The effect of temperature (35–55 °C), time (10–240 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
1
15
1
Order By: Relevance
“…Taiwo et al (2003) observed a decrease in hardness of PEF-treated (1.2 kV/cm, 350 µs) strawberry halves (1200 V/cm; 350 µs) followed by OD for 4 h in binary (sucrose, NaCl) solution. In contrast to these results, Dermesonlouoglou et al (2020) reported that the hardness values of OD samples were higher than the respective values of fresh-cut pumpkin samples. This increase of hardness in final dried plant material could be observed after longer OD times due to the penetration of Ca 2+ into the plant tissue (de Souza Silva et al, 2011;Dermesonlouoglou et al, 2016aDermesonlouoglou et al, , 2016b.…”
Section: Pef and Od Effect On Air-dried Pumpkincontrasting
confidence: 60%
See 1 more Smart Citation
“…Taiwo et al (2003) observed a decrease in hardness of PEF-treated (1.2 kV/cm, 350 µs) strawberry halves (1200 V/cm; 350 µs) followed by OD for 4 h in binary (sucrose, NaCl) solution. In contrast to these results, Dermesonlouoglou et al (2020) reported that the hardness values of OD samples were higher than the respective values of fresh-cut pumpkin samples. This increase of hardness in final dried plant material could be observed after longer OD times due to the penetration of Ca 2+ into the plant tissue (de Souza Silva et al, 2011;Dermesonlouoglou et al, 2016aDermesonlouoglou et al, , 2016b.…”
Section: Pef and Od Effect On Air-dried Pumpkincontrasting
confidence: 60%
“…Osmotic dehydration (OD) is an alternative dehydration technology that targets at the diffusion of water out of the food product and the diffusion of solids (through the semipermeable membrane) into the product by immersion of the food product into a concentrated solution (Ahmed et al., 2016). The combination of mild OD conditions and the selective enrichment of the osmosed tissue with solutes of the osmotic solution (humectants including carbohydrates, salts, and other small molecular weight compounds) produce a modified food commodity with desired quality attributes (Ciurzyńska et al., 2016; Dermesonlouoglou et al., 2020). OD can lead to shelf‐life stable intermediate moisture products (IMF) (Qui et al., 2019) maintaining sensory characteristics (color, texture, and flavor) of fresh food products and enhancing the nutritional value.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular osmotic agent for fruit is sucrose [13][14][15]. However, the current trends in OD include the application of alternative osmotic substances [16]. One trend is the use of ingredients with high nutritional value, for example, fruit juice concentrates [17][18][19], while the other is the use of ingredients with a low glycaemic index such as polyols [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…According to the mechanism of the OD process, the reduced amount of freezable water content and water activity and therefore the inferior availability of water for the degradative reactions and growth of microorganisms can guarantee a higher microbial stability [34,[86][87][88] For example, pumpkin subjected to OD process in different osmotic solutions, after 90 days of storage was characterized by low values up to 3-4 log CFU, while the initial microbial counts of total aerobic bacteria, yeast and molds after OD process were at undetectable levels (<10 CFU/g) [89]. Moreover, Nowacka et al [39] studied the growth of mesophilic aerobic bacteria and yeast in cranberries subjected to the UOD process with different osmotic solutions and stored for eight weeks at the temperature of 10 • C. They noticed that the sucrose solution enabled for longer shelf-life in comparison to other two solutions used (trehalose solution or reduced concentration of sucrose with the addition of steviol glycosides), due to the lower water activity achieved in the final products.…”
Section: Effect Of Sonication and Osmotic Dehydration Process On Microbial Growthmentioning
confidence: 99%